GPX modulation promotes regenerative axonal fusion and functional recovery after injury through PSR-1 condensation - Su-Hyuk Ko; Kyung-Ah Cho; Xin Li; Qitao Ran; Zhijie Liu; Lizhen Chen (Nature Communications)
Abstract Axonal fusion represents an efficient way to recover function after nerve injury. However, how axonal fusion is induced and regulated remains largely unknown. We discover that ferroptosis signaling can promote axonal fusion and functional recovery in C. elegans in a dose-sensitive manner. Ferroptosis-induced lipid peroxidation enhances injury-triggered phosphatidylserine exposure (PS) to promote axonal fusion through PS receptor (PSR-1) and EFF-1 fusogen. Axon injury induces PSR-1 condensate formation and disruption of PSR-1 condensation inhibits axonal fusion. Extending these findings to mammalian nerve repair, we show that loss of Glutathione peroxidase 4 (GPX4), a crucial suppressor of ferroptosis, promotes functional recovery after sciatic nerve injury. Applying ferroptosis inducers to mouse sciatic nerves retains nerve innervation and significantly enhances functional restoration after nerve transection and resuture without affecting axon regeneration. Our study reveals an evolutionarily conserved function of lipid peroxidation in promoting axonal fusion, providing insights for developing therapeutic strategies for nerve injury.